2017
DOI: 10.1021/acsami.7b12755
|View full text |Cite
|
Sign up to set email alerts
|

Wireless Acoustic-Surface Actuators for Miniaturized Endoscopes

Abstract: Endoscopy enables minimally invasive procedures in many medical fields, such as urology. However, current endoscopes are normally cable-driven, which limits their dexterity and makes them hard to miniaturize. Indeed, current urological endoscopes have an outer diameter of about 3 mm and still only possess one bending degree-of-freedom. In this article, we report a novel wireless actuation mechanism that increases the dexterity and that permits the miniaturization of a urological endoscope. The novel actuator c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 36 publications
0
16
0
Order By: Relevance
“…We attribute the shift between the experimental and numerical resonant frequency of the microbubble to the surface tension-induced stiffness component, which is missing in the simulation environment (SI Appendix, section S2). Unlike other reported bubble-based swimmers in the literature (12,22,30) with bubble radius bigger than 30 μm, at scales related to our design the effect of surface tension is significant. Indeed, using a scaling analysis, we found that the ratio of surface tension to volumetric pressure change is around 3 (SI Appendix, section S2).…”
Section: Characterization Of the Microbubble Resonance Frequency Andmentioning
confidence: 61%
“…We attribute the shift between the experimental and numerical resonant frequency of the microbubble to the surface tension-induced stiffness component, which is missing in the simulation environment (SI Appendix, section S2). Unlike other reported bubble-based swimmers in the literature (12,22,30) with bubble radius bigger than 30 μm, at scales related to our design the effect of surface tension is significant. Indeed, using a scaling analysis, we found that the ratio of surface tension to volumetric pressure change is around 3 (SI Appendix, section S2).…”
Section: Characterization Of the Microbubble Resonance Frequency Andmentioning
confidence: 61%
“…Various SAW devices have the potential to be commercialized into flexible diagnostic platforms that may be transformed into wearable devices. A collaboration between different SAW and streaming-driven tweezers can push the boundaries of their traditional usage in microfluidics, to design of acoustically driven surgical devices [140]. Lastly, we discuss self-propelling micro-agents with on-board vibrational units designed to resonate at specific acoustic frequencies.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, any contaminants or dirt having the size similar or smaller than microrobots could increase the risk of stiction which can perturb their sustainable and robust motions and functionalities. Various microrobots have been studied and demonstrated in their propulsions remotely powered by optical [3][4][5], acoustic [6][7][8], chemical [9,10] or magnetic energy [11][12][13][14]. The microfluidic channel applications could amplify such risk of stiction due to increased channel walls influences.…”
mentioning
confidence: 99%